(untitled) (Research, Society and Development, 2024)
There is an increasing need to discuss the topic of female entrepreneurship and its relevance in society today. Due to a lack of knowledge, clarification, and even sexism, women do not have the same rights and opportunities in practice as men. Therefore, it is necessary to shed light on this topic, which directly and indirectly impacts many people. The objective of this study is to present a conceptual model from the authors’ perspective for discussing the female entrepreneurship process through a qualitative, theoretical, and conceptual study supported by a narrative literature review. Therefore, an indirect documentary review methodology of a qualitative nature was used, followed by a theoretical discussion essay, in order to describe the characteristics of a given population and identify the relationship between the variables, enabling the construction of hypotheses that can generate future studies in this line of study.